Characterization of Nb3Sn Superconducting Strands under Wide Range Pure-Bending Strain. - Mallon, Philip. (2017)
Abstract: Nb3Sn superconducting wire is sensitive to strain, which degrades electromagnetic performance. The substantial operation degradations found during ITER model coil tests of high current Cable-in-Conduit Conductors have given rise to research aimed at understanding the mechanisms behind the degradations due to bending, transverse, and axial strains. The degradation of a single Nb3Sn strand under pure bending is the focus of this thesis. Pure bending tests have been conducted to quantify the degradation for the ITER Nb3Sn strands. Based on the previously developed pure-bending sample holder for up to 0.8%, two improved types of sample holders were developed to cover pure-bending strains up to 1.4%. The test probe held two sample holders, with two strand samples in each sample holder. Bending errors and Lorentz force effects on the sample holders were evaluated. Critical current measurements as a function of bending strain between 0 and 1.4% were performed for ITER Luvata and Oxford internal tin wires at 15 T at the National High Magnetic Field Laboratory, FL. It was found that eliminating the thin support walls used in the low bending sample holder allows for the desired higher strains to be applied to the sample while still supporting the strand against the Lorentz load. Under a strain of 1.3%, both types of samples experienced about a 60% loss in critical current. During cyclic bending up to 1.4%, Luvata samples lost about 50% their critical current performance.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Luisa Chiesa.; Committee: Makoto Takayasu, and Gary Leisk.; Keyword: Mechanical engineering.